Inflammatory pigmented paravenous retinochoroidal atrophy. Issue 6 (June 1989) - Yamaguchi, K.; Hara, S.; Tanifuji, Y.; Tamai, M.
Abstract : A 47-year-old Japanese man had a progressive degeneration of the retina and choroid along the retinal veins associated with uveitis of two years' duration. The lesion was characteristic of paravenous retinochoroidal atrophy: a contiguous atrophy of the retinal pigment epithelium and choroid of one-half to one disc diameter in size was present along most of the veins from the posterior pole to the far periphery. Fluorescein angiography showed a window defect in the retinal pigment epithelium, with hyperfluorescence representative of retinal pigment epithelium and choriocapillaris degeneration. Good visual acuity was attained after extracapsular cataract extraction for complicated cataract and vitrectomy for severe vitreous opacity had been performed in both eyes. The cause of this new inflammatory disease was unknown.